Conditionality of COVID-19 vaccine acceptance in European countries. Issue 9 (23rd February 2022) - Heyerdahl, Leonardo W.; Vray, Muriel; Lana, Benedetta; Tvardik, Nastassia; Gobat, Nina; Wanat, Marta; Tonkin-Crine, Sarah; Anthierens, Sibyl; Goossens, Herman; Giles-Vernick, Tamara
Highlights: Mixed-method survey studied expected COVID vaccine uptake in 7 European countries. Projected COVID vaccine acceptance by country ranged from 44% to 66%. Explicit COVID vaccine acceptance or rejection was conditional. Study finds concerns about vaccine safety and authorities' competence and honesty. Study suggests that vaccine conditionality is dynamic, and that safety concerns persist. Abstract: The COVID-19 vaccine rollout has offered a powerful preventive measure to help control SARS-CoV-2 transmission. Nevertheless, long-standing public hesitation around vaccines heightened concerns that vaccine coverage would not achieve desired public health impacts, particularly in light of more contagious variants. This cross-sectional survey was conducted online just before the European vaccine rollout in December 2020 among 7000 respondents (aged 18–65) in Belgium, France, Germany, Italy, Spain, Sweden, and Ukraine. The survey included open text boxes for fuller explanation of responses. Overall, 56.9% of respondents would accept a COVID-19 vaccine, 19.0% would not, and 24.1% did not know or preferred not to say. By country, between 44% (France) and 66% (Italy) of respondents would accept a COVID-19 vaccine. Respondents expressed conditionality in open responses, voicing concerns about vaccine safety and mistrust of authorities. We highlight lessons learned about the dynamism of vaccine conditionality and persistence of safety concerns.